Zinc in potato production - Urano, Charles Y., author; Foskett, Richard L., advisor (Colorado State University. Libraries, 1966)
Zinc deficiencies have been reported from the states of Washington, Idaho, North Dakota and Texas. The deficiencies are reported to be localized in areas where the parent material of soil is low in zinc content or where the topsoil has been removed by landleveling or lost through erosion. There is evidence that zinc plays an important role in the synthesis of tryptophane, an amino acid that is necessary for the formation of the growth hormone, auxin. Other data indicate that zinc is essential for the metabolic activities of some enzymes. No difficulty has been reported in correcting the deficiency. Foliage and soil applications of zinc sulfate have given a yield response. Some workers indicate that a broadcast application and incorporation with a disc will produce a yield response where other methods will not. Foliage symptoms and response to method of application seems to differ with varieties.
Covers not scanned.
Keywords: Potatoes; Plants -- Effect of zinc on